Calculation of Potential Barriers and Blocking Temperatures of Small Pseudo–Single-DomainParticles by Micromagnetism Methods - V. P. Shcherbakov; N. K. Sycheva (Учёные записки Казанского университета: Серия Естественные науки)
Numerical simulation of the process of remagnetization of small pseudo–single-domain magnetite particles (Тc = 580°С) was performed. The particles are cylindrical in shape, with a height h of 60–350 nm and a height-to-diameter ratio of 1.29. This geometry enables preferential anisotropy of the shape, causing the magnetic moment of the particle to align along the cylinder’s axis in a stable state. As the size increases, the domain structure shifts from the single-domain state (60 nm) to the flower mode (h = 70–85 nm), and then to a vortex structure. Particles in the range of h = 75–250 nm are remagnetized through a vortex state, with the axis aligned along their diameter. In the range of h = 300–350 nm, at the top of the potential barrier, the domain structure transforms from a single vortex to a multi-vortex configuration. The blocking temperatures Tb of the particles vary from 520 to 580°C, while the dependence Тb(h) is non-monotonic and manifests a “pit” at h = 90–140 nm. At the same time, at h = 300–350 nm, Tb values differ from by Тс  no more than 1°C. At h = 100 nm, the ratio of magnetic energy in the external field B of the order of the earth to thermal energy at T = Tb reaches 1. This suggests a strong nonlinearity of the TRM(B) dependence even in such small fields and particle sizes. The results obtained highlight the need to revise the existing micromagnetic models by taking into account the specific shape and deficiency of the crystal structure of particles in order to bring them in line with the properties of actual ferrimagnets present in rocks.